Regional Expenditure Dynamics and its Impact on Economic Growth: Magetan Regency 2010-2019 (Open Society Conference, 2023)
This article presents the research results that aim to explain the impact of regional spending on economic growth in Magetan Regency 2010–2019 by utilizing secondary data published by the Central Bureau of Statistics (BPS). Regional spending is district government spending aimed at financing the running of regional administration by the district authority. This study uses an associative quantitative approach. The data analysis technique used is the Pearson Product Moment, using data carried out by some previous tests, namely data quality tests in the form of validity and reliability as well as data suitability tests or classic assumption tests. The statistical test produces a Pearson Product Moment correlation rate of -0.788. Furthermore, the significance test using the t-test produces a t-count of -3.61, lower than the t-table of 1.833. These results indicate that regional expenditure has a negative effect on economic growth, meaning that if regional expenditure increases, economic growth decreases. It contradicts the theory that the higher the regional spending, the higher the economic growth. A deeper search through a series of in-depth interviews found two important factors causing this negative correlation. First, most office workers, both in the public and private sectors, spend their funds, both for household consumption and for investment, outside the Magetan Regency area, likewise with the consumption behavior of the Magetan Regency government and the recipients of construction work from the Magetan Regency government and from the private sector. They also spend funds to procure tools, machines, and building materials outside Magetan Regency.